CORONA: Our Weakness proved to be our Strength - Bhol, Seema Gupta (Journal of Advanced Research in HR and Organizational Management, 2020)
Corona virus crisis affected almost every country in the world. Different countries are trying to handle in different ways. As suggested by experts, social distancing is one of the major tools to contain the spread of pandemic. Lockdowns and shutdowns are imposed by many Governments to enforce social distancing. Thus people are facing double problems. One is to remain safe during pandemic and other one is to ensure smooth supply of necessities. The present Paper compares situation of India with other developed countries and try to analyze how age old Indian practices, life style, social structure is helping Indians to fight with the crisis.